Implementation of Role Playing Method to Increase Self-Confidence of Early Childhood at RA Nurul Hikmah Lenteng - Farida; Mediyana, Mediyana; Dewi Pusparini (STIT Attaqwa, 2025)
This study aims to determine the application of the role-playing method in increasing the self-confidence of early childhood at RA Nurul Hikmah Lenteng. The background of this study is the low courage of children to appear and actively participate in learning activities. Children tend to be passive, reluctant to speak in front of friends, and depend on friends in group activities. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The subjects in this study were children in group B (aged 5–6 years) who participated in role-playing activities for six meetings. The results of the study showed that the role-playing method was able to increase children's self-confidence, which was marked by the courage to appear, the ability to express opinions, and active involvement in the group. Children also began to show initiative and the ability to interact socially more independently. Thus, the role-playing method can be used as an alternative effective learning strategy in developing the social-emotional aspects of early childhood, especially in building self-confidence from an early age.